2020
DOI: 10.1097/meg.0000000000001958
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy and safety of direct oral anticoagulants in the treatment of portal vein thrombosis

Abstract: Objective The purpose of this study was to evaluate the efficacy and safety of direct oral anticoagulants vs. warfarin for portal vein thrombosis treatment. Methods This was a single-center, retrospective study. Adult patients initiated on a direct oral anticoagulant or warfarin for treatment of a new portal vein thrombosis were included. The primary failure outcome was the absolute difference in recurrent thromboembolic events 90 days following initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
(76 reference statements)
0
15
0
1
Order By: Relevance
“…Table 1 shows the author, year, type of study, study group, control group, primary and secondary outcomes, and adverse outcomes of the original studies [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 shows the author, year, type of study, study group, control group, primary and secondary outcomes, and adverse outcomes of the original studies [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, DOACs were associated with fewer episodes of major bleeding [24]. A study involving both cirrhotic and non-cirrhotic patients with PVT showed better outcomes in patients treated with DOACs compared to warfarin in terms of treatment failure and adverse events [26]. Thus, the use of DOACs for the treatment of PVT is evolving but remains contentious.…”
Section: Discussionmentioning
confidence: 99%
“…Danach schließt sich das weitere therapeutische Work-up an. Die Datenlage bezüglich der Auswahl der richtigen Antikoagulation ist bislang rudimentär und stützt sich fast ausschließlich auf retrospektive Daten [12][13][14][15][16]. Grundsätzlich gilt es aber zu berücksichtigen, dass der Einsatz von oralen Antikoagulanzien (DOAK) stets "off label" erfolgt.…”
Section: Auswahl Des Antikoagulansunclassified
“…A first issue regards the quality of the studies included in the meta-analysis [2][3][4][5][6][7][8][9][10][11][12] . Out of eleven studies involving 552 subjects (217 treated with DOAC and 335 treated with VKA), one only was a randomized controlled study (RCT) [4] while the others were retrospective, small or relatively small cohort studies, all with their in-herent biases.…”
mentioning
confidence: 99%
“…Only five of 11 studies compared the outcome of PVT recanalization [ 3 , 4 , 7 , 8 , 10 ] with a pooled rate favouring DOAC over VKA, but with heterogeneity substantial and sensitive to study design, as the benefit of DOAC was only observed within the RCT [4] , but not among the cohort studies. As for the other outcomes, only three studies compared the risk of PVT progression [ 3 , 4 , 7 ], only four compared the risk of major bleeding [5][6][7][8] , and only two compared the risk of variceal bleeding [ 3 , 5 ] or death [ 4 , 8 ].…”
mentioning
confidence: 99%